Surfacing time, availability bias and abundance of humpback whales in West Greenland - Heide-Jørgensen, M. P.; Laidre, K. L. (J. Cetacean Res. Manage., 2023)
Visual aerial surveys of large whales are negatively biased unless correction factors are developed to correct the availability of whales at the surface. One method for developing a correction factor for this bias is by instrumenting whales with recorders that measure the amount of time spent at the surface. Thirty-one SLTDRs (three different models) were deployed on humpback whales (Megaptera novaeangliae) in West Greenland in May and July 2009–10. The SLTDRs recorded the proportion of a 6 hour period that the whales spent at or above 2m depth (defined here as surfacing time). This depth is considered to be the maximum depth that humpback whales are reliably detected from the air on visual aerial surveys in West Greenland. Eighteen transmitters provided data on the surfacing time and the drift of the pressure transducer. The average surfacing time for whales over the study period during the two 6 hour periods with daylight was 28.3% (CV = 0.06). Six whales met the data filtering criteria and had low drift in transmitter depth. Their average surface time was 33.5% (CV = 0.10). Previous analyses of visual aerial survey data have shown that the amount of time whales are available to be seen by observers is not an instantaneous process. Therefore, surface time must be corrected for a positive bias of about 10% when developing a correction factor for availability bias. This increases the availability in this study to 36.8% (CV = 0.10). The most recent survey of humpback whales in West Greenland was conducted in 2007 and corrections using this availability factor produce fully corrected abundance estimates of 4,090 (CV = 0.50) for mark-recapture distance sampling analysis and 2,704 (CV = 0.34) for a strip census abundance estimate. These estimates are about 25% larger than previous estimates from the same survey.